A study of the coffee shop as a third place for university students - Bernardo, Erika Anna B.
Abstract This study determined whether interior design plays a role in encouraging university students to gather in coffee shops. Using a qualitative approach of research, it also analyzed the context of the coffee shops as a third place based on the viewpoint of university students and sought to find out if interior design had an influence on its status as a third place. The researcher selected university students who identified themselves as frequent coffee shop goers through non-probability snowball sampling. Respondents were students currently enrolled in the universities within the vicinity of the coffee shops. The top two coffee shops they patronized were likewise selected for the study namely, (1) Starbucks Coffee and (2) The Coffee Bean and Tea Leaf, both located along Katipunan Avenue, Quezon City. Non-participant observation was conducted in the selected coffee shops while focused interviews were conducted with ten respondents for each. Findings revealed that the coffee shops possess the characteristics of a third place as the sociologist Ray Oldenburg (1999) conceptualized, and students potentially establish coffee shops as their third place. The study suggests that interior design does influence positive experiences for the students which lead them to patronize coffee shops. The results of this study may serve as a guide in designing spaces that may serve as third places, and in understanding how interior design affects experiences within these places. Furthermore, the study may contribute to the enhancement of the BS Interior Design curriculum, specifically in the course on hospitality design.